ANALISIS KESIAPAN PKBM DALAM MENGHADAPI AKREDITASI BERBASIS SISPENA 2.0 DI KABUPATEN REJANG LEBONG - Rola Febrianti; Wahiruddin Wadin; Bayu Pradikto (UNIB Press, Universitas Bengkulu, 2020)
The purpose of this research is to measure the percentage of management readiness of PKBM in following accreditation. This research was a quantitative descriptive study using a questionnaire as the research instrument. The sample in this study was 8 respondents who were PKBM managers in Rejang Lebong Regency. The finding obtained from the results of the PKBM readiness in registering institutions in SISPENA showed a percentage of 84.28571% so that it was included in the category of very ready to register their institutions at SISPENA. For the readiness of 8 standard documents, the research results obtained show a percentage of 71.25673% so that it was included in the quite ready category. For performance readiness/ implementation of activities, the results of the study showed a percentage of 62.32039% so that it was included in the category of not ready. Based on research findings, it was known that the obstacles in preparing the accreditation process were cost and human resources. The conclusion from this study was that PKBM managers in Rejang Lebong Regency were very prepared to register their institutions in SISPENA because all PKBM already have an NPSN as the main requirements for admission to SISPENA. In addition, it was also known that PKBM managers are quite prepared in preparing 8 standard documents because on average PKBM managers already have 8 standard documents. The manager of PKBM was not ready to prepare the performance/implementation of activities because the data found was not in accordance with 8 standard documents.